PCL retention demonstrates better functional scores and gait patterns in total knee arthroplasty using a medial congruent insert—a prospective study - Rajgopal, Ashok; Kumar, Sumit; Singh, Manish Kumar; Aggarwal, Kalpana (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2023)
Purpose Despite Total Knee Arthroplasty (TKA) being one of the most successful procedures for end stage arthritis, nearly 20% of patients undergoing this procedure remain dissatisfied. Various design options have been introduced to reduce this cohort of patients. One such option has been the introduction of the medial congruent (MC) polyethylene design. This study was undertaken to evaluate outcome measures and gait analysis in patients undergoing bilateral single stage TKA where the posterior cruciate ligament (PCL) was retained or excised in contralateral knees. Methods 60 bilateral TKA’s were performed by a single surgeon using a MC design option from July to Sep 2021. The study lots included patients between the ages of 55 and 70 years with fixed varus deformity of degenerative aetiology, and Kellgren Lawrence Grade 3 and 4 radiological changes. Exclusion criteria were previous surgery to the lower extremities, sero positive arthropathies, post traumatic arthritis, valgus deformity, flexion contractures > 20°, and any pre-existing pathology impacting gait, e.g., poliomyelitis, or neuromuscular disorders. The PCL was retained or sacrificed on contralateral sides for the purpose of this study. Functional scores, outcomes and gait analysis on level and gradient walking were evaluated at a follow-up of 18 months. Results At 18, months the Range of Motion (ROM) improved from a preoperative value of 97.3 ± 11.5 to 110.3 ± 6.1 on the PCL retained side (MC-PCL) and from 96.5 ± 10.8 to 113 ± 5.8 on the PCL excised side (MC-PCLX). Knee Society Score (KSS-2011) improved from a preoperative value of 21.2 ± 4.5 to 89.8 ± 3.4 at 18 months postoperatively on the MC-PCL side and from 21.5 ± 4 to 88.2 ± 3.7 on the MC-PCLX side. Forgotten Joint Score (FJS-12) was 8.8 ± 0.7 on the MC-PCL side and 8.1 ± 0.9 on the MC-PCLX side 18 months after surgery. Our gait analysis evaluation demonstrated a lower forefoot pressure in the MC-PCL group in comparison to the MC-PCLX group when subjects were made to walk on a 30° upward incline. This difference was found to be statistically significant. Conclusion In this study, while ROM was greater in the MC-PCLX study lot, patient satisfaction was higher in the MC-PCL study lot. Gait assessment demonstrated lower forefoot pressure while ascending an incline of 30° in the MC-PCL study lot as compared to the MC-PCLX study lot approximating normal gait patterns. Level of evidence II.